Democracy against parties? Party system deinstitutionalization in Colombia - Dargent Bocanegra, Eduardo (2013)
This article argues that in Colombia, decentralization and electoral reforms adopted in the late 1980s and in the 1991 Constitution – designed to improve democratic quality – brought about a gradual deinstitutionalization of this country’s traditional party system as an unintended consequence. Building upon resource-based theories of party configuration, we contend that in developing countries, where resources are usually crucial for party aggregation, democratizing reforms designed to distribute power and resources in the political system can reduce local candidates’ incentives to join and remain loyal to political parties, particularly when those parties’ reputations are weak. In Colombia, these reforms (i) reduced the power of intermediate-level party leaders over the distribution of selective incentives, making these leaders less important for local politicians, and (ii) gave more political and financial autonomy to local candidates, reducing their need to join parties in order to advance their electoral goals. As a result, party cohesion and discipline become difficult to maintain, and the party system gradually deinstitutionalizes.